2021
DOI: 10.1002/ldr.3863
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different cropping systems on the land nutrient index, microbial diversity, and soil quality

Abstract: In the last two decades, the productivity of the rice–wheat growing system (RWGS) in the upper Indo‐Gangetic Plains of India has come to a plateau, and, as a result, farmers are now shifting to other crop growing systems (cropping sysytems) to achieve a higher net productivity. Inclusion of other cropping systems in place of the rice–wheat system affects overall crop productivity; however, there is dearth of information with respect to nutrient index (NI), microbial diversity, and soil quality. This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Crop rotation can effectively improve soil nutrient content and enzyme activity [17][18][19] and change the diversity and structure of soil microbial communities [20,21] through the impacts of root exudates and crop residues, which are effective at reducing crop succession barriers [22]. One relevant study suggested that bacteria and fungi in soils generally account for more than 90% of all the soil microbial population [23], and some organic matter conversion processes in soils are controlled by soil microbial communities [24][25][26]. Soil microbial diversity can be used as an index for evaluating soil quality [26,27] and can be considered an important indicator for assessing soil stability under various environmental influences [28].…”
Section: Introductionmentioning
confidence: 99%
“…Crop rotation can effectively improve soil nutrient content and enzyme activity [17][18][19] and change the diversity and structure of soil microbial communities [20,21] through the impacts of root exudates and crop residues, which are effective at reducing crop succession barriers [22]. One relevant study suggested that bacteria and fungi in soils generally account for more than 90% of all the soil microbial population [23], and some organic matter conversion processes in soils are controlled by soil microbial communities [24][25][26]. Soil microbial diversity can be used as an index for evaluating soil quality [26,27] and can be considered an important indicator for assessing soil stability under various environmental influences [28].…”
Section: Introductionmentioning
confidence: 99%
“…It seems the interaction effect of seasons and crop species by crop species on soil properties due to confounding effect because the crops did not significantly affect the chemical properties of soils (except for organic matter content and acid-phosphatase activity). Previous studies had shown that soil enzyme activity was strongly influenced by crop species ( Singh et al., 2021 ). However, crop species only affected acid-phosphatase activity in this study ( P <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The soil nutrient index value is a measure of the capacity of soil to supply nutrients to plants which also assesses the long-term impact of different crop-grown systems on changes in nutrient patterns ( Amara et al., 2017 ; Singh et al., 2021 ). In this study, it was found that most of the examined soils are in low to medium pH index.…”
Section: Discussionmentioning
confidence: 99%